2016
DOI: 10.3389/fnagi.2016.00319
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Activity in the Healthy Elderly Is Associated with Larger Plasticity in Memory Related Brain Structures and Lower Systemic Inflammation

Abstract: Cognitive abilities decline over the time course of our life, a process, which may be mediated by brain atrophy and enhanced inflammatory processes. Lifestyle factors, such as regular physical activities have been shown to counteract those noxious processes and are assumed to delay or possibly even prevent pathological states, such as dementing disorders. Whereas the impact of lifestyle and immunological factors and their interactions on cognitive aging have been frequently studied, their effects on neural par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…We used the episodic memory paradigm and voxel placement described by Thielen et al (2016) to ensure that the MRS voxels were placed in brain regions involved in the memory task. The faceprofession encoding task was performed within the scanner.…”
Section: Memory Paradigmmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the episodic memory paradigm and voxel placement described by Thielen et al (2016) to ensure that the MRS voxels were placed in brain regions involved in the memory task. The faceprofession encoding task was performed within the scanner.…”
Section: Memory Paradigmmentioning
confidence: 99%
“…Since Thielen et al (2016) showed that the memory task used in the present study activates brain regions in the mPFC and precuneus we placed the MRS voxels in this brain regions. The voxels were placed according to anatomical landmarks.…”
Section: Mrs Voxel Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…[32]. Other studies have shown that physically active individuals have better spatial memory [31], episodic memory [33], and short-term memory [34]. Some authors showed that after following physical training, participants achieved the same pattern of results as physically active participants and exhibited better resistance to interference [7].…”
Section: Introductionmentioning
confidence: 99%